2015
DOI: 10.3846/16487788.2015.1107306
|View full text |Cite
|
Sign up to set email alerts
|

Technological Processes and Quality Control in Aircraft Engine Maintenance

Abstract: The paper analyzes some issues which refer to the quality assessment of operations performed by aviation specialists when maintaining aircraft. Technological processes and quality control in aircraft engine maintenance are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Under the prism of this study, there is a lack of understanding that maintainability, reliability, and risk, in the comprehension presented by (Dhillon 2006) and (Smith 2005) mentioned above, deal with probabilities as an objective characteristic of an engineering system in the broadest sense, thus, losing from the sight the importance of individuals' subjective characteristics which are the preferences of alternatives. Now, considering the topical problems of the aviation industry in more detail, it should be noted that this fact ought to be taken into account when carrying out aircraft maintenance (Dmitriev et al 2015). Considering the possible ways, methods, and techniques for maintenance process improvement, a responsible person driven by his/her own personal, individual, and subjective, scale of the preferences distribution system makes the final decision concerning, in his/her opinion, some better options, keeping in mind such indispensable issues as fight safety and airworthiness levels but not only those.…”
Section: Introductionmentioning
confidence: 99%
“…Under the prism of this study, there is a lack of understanding that maintainability, reliability, and risk, in the comprehension presented by (Dhillon 2006) and (Smith 2005) mentioned above, deal with probabilities as an objective characteristic of an engineering system in the broadest sense, thus, losing from the sight the importance of individuals' subjective characteristics which are the preferences of alternatives. Now, considering the topical problems of the aviation industry in more detail, it should be noted that this fact ought to be taken into account when carrying out aircraft maintenance (Dmitriev et al 2015). Considering the possible ways, methods, and techniques for maintenance process improvement, a responsible person driven by his/her own personal, individual, and subjective, scale of the preferences distribution system makes the final decision concerning, in his/her opinion, some better options, keeping in mind such indispensable issues as fight safety and airworthiness levels but not only those.…”
Section: Introductionmentioning
confidence: 99%
“…We selected these tasks because of their recurrence and representativeness among other maintenance tasks of the helicopter and plane, particularly, regarding the parameters of posture, gestures, and effort. Various studies in the aviation field have confirmed the interest of the engine part in performing HFE analysis (Amundarain et al, 2003; Dmitriev, Burlakov, Popov, & Popov, 2015; Geng et al, 2013), particularly because of the variability of tasks and work postures (Lockett & Arvanitopoulos-Darginis, 2017; Lu, Zhou, & Li, 2015; Shi & Liu, 2012). In addition, the tasks selected in our study are included as part of regular and mandatory maintenance activities—the most frequent task (Task 1), which is performed every week, and the least frequent task (Task 7), which occurs once a month.…”
Section: Methodsmentioning
confidence: 96%
“…It has been proven that technological processes and quality control of aircraft engine maintenance are key factors for advancing the process of continuing air-worthiness support. [7] Unlike many other modern high-tech areas like car and combustion engine assembly lines and production lines of electric motors, the assembly and maintenance of jet engines is quite conservative. In production and in service many manual labor operations are used.…”
Section: Introductionmentioning
confidence: 99%